Light Polarization in Tunnel Junction Injected UV Light‐Emitting Diodes. Issue 7 (4th March 2022) - Duboz, Jean-Yves; Fan Arcara, Victor; Kessaci, Cynthia; Vézian, Stéphane; Damilano, Benjamin
Abstract : The polarization of the light emitted by an ultraviolet light‐emitting diode (LED) has a direct impact on the device performance: a transverse electric polarization of the emission is preferred for extraction from the surface of the diode grown along the c axis. While this is the case for most UV LEDs grown on AlN, this state of events could be called into question when a tunnel junction (TJ) is added to make up for the poor p doping in Al‐rich (Al, Ga)N and improve the hole injection. Indeed, nitride‐based TJs mainly inject holes with a Γ7 symmetry, which could lead to transverse magnetic polarization of the light emitted by the diode. We have experimentally investigated this important issue and delivered a clear answer to this question. Abstract : A tunnel junction (TJ) added on the p side of an UV light‐emitting diode (LED) does not modify the polarization of the emitted light. The transverse electric/transverse magnetic ratio in the LED with a TJ remains the same as in the LED without TJ, which was close to unity. This remains true at any injection current.